MUHAMMADIYAH YOUTH MOVEMENT ENTREPRENEUR SCHOOL, KURSUS KEWIRAUSAHAAN SINGKAT UNTUK REMAJA AKTIVIS ORTOM MUHAMMADIYAH MALANG - Ahmad Shobrun Jamil (Universitas Muhammadiyah Mataram, 2020)
ABSTRAKMuhammadiyah Youth Movement Enterpreneur Malang bertujuan untuk melatih para calon wirausahawan muda aktivis Organisasi Otonom (ORTOM) Muhammadiyah di kota Malang. Untuk membuat sistem yang baku maka akan dilaksanakan fokus grup diskusi dengan beberapa pakar ahli dalam bidang pendidikan maupun dalam bidang praktisi entrepreneurship di Malang yang kemudian disusun dalam sebuah naskah standar operasional prosedur dan dijadikan acuan dalam pelaksanaan AMM entrepreneur school selanjutnya. Selain itu akan dibuat berbagai komponen pembelajaran mulai rancangan pembelajaran pelaksanaan pembelajaran perangkat pelaksanaan pembelajaran sistem evaluasi. Pelatihan memberikan dampak yang positif bagi peserta. Mereka semakin tahu dengan skema kanvas bisnis dan model bisnis modern. Dan hal-hal diatas memberikan beberapa pelajaran dan rekomendasi untuk pelatihan batch mendatang diperlukan pengelompokan usaha yang sama dalam starting point usaha dan tingkat pengetahuan peserta sehingga materi dapat diberikan dengan maksimal. Kata Kunci: pengabdian; entrepreneur; AMM; pembelajaran; pelatihan; usaha. ABSTRACTMuhammadiyah Youth Entrepreneur Movement Malang aims to train aspiring young entrepreneurial activists of the Muhammadiyah Autonomous Organization (ORTOM) in Malang city who have small businesses or micro businesses in their respective places to be able to improve the quality and quantity of their business. To create a standard system, focus group discussions will be carried out with several expert experts in the field of education and in the field of entrepreneurship practitioners in Malang which are then compiled in a standard operating procedure script which is then used as a reference in the implementation of the next AMM entrepreneur school. In addition, various learning components will be made starting from the learning design of the learning implementation of the evaluation system learning implementation tools. The training has a positive impact on the participants. They are increasingly familiar with business canvas schemes and modern business models. And the things above provide some lessons and recommendations for the next batch of training, it is necessary to group the same efforts in starting the business points and the level of knowledge of the participants so that the material can be given optimally. Keywords: dedication; entrepreneur; AMM; learning; training; business.